2014
DOI: 10.1111/tpj.12562
|View full text |Cite
|
Sign up to set email alerts
|

Phosphorylation of photosystem II core proteins prevents undesirable cleavage of D1 and contributes to the fine‐tuned repair of photosystem II

Abstract: SUMMARYPhotosystem II (PSII) is a primary target for light-induced damage in photosynthetic protein complexes. To avoid photoinhibition, chloroplasts have evolved a repair cycle with efficient degradation of the PSII reaction center protein, D1, by the proteases FtsH and Deg. Earlier reports have described that phosphorylated D1 is a poor substrate for proteolysis, suggesting a mechanistic role for protein phosphorylation in PSII quality control, but its precise role remains elusive. STN8, a protein kinase, pl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
47
0
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 64 publications
(49 citation statements)
references
References 44 publications
0
47
0
2
Order By: Relevance
“…4a, G), which reflects reformation of PSI-PSII complexes. It has been suggested that phosphorylation of LHC and PSII core components is involved in the migration of photosystems between grana stack and stroma thylakoid regions 18 . To investigate the role of phosphorylation of these proteins, we examined the delayed fluorescence of mutants defective in the phosphorylation of individual proteins.…”
Section: Resultsmentioning
confidence: 99%
“…4a, G), which reflects reformation of PSI-PSII complexes. It has been suggested that phosphorylation of LHC and PSII core components is involved in the migration of photosystems between grana stack and stroma thylakoid regions 18 . To investigate the role of phosphorylation of these proteins, we examined the delayed fluorescence of mutants defective in the phosphorylation of individual proteins.…”
Section: Resultsmentioning
confidence: 99%
“…It has been demonstrated that the FtsH protease is composed of type A (FtsH1 and FtsH5) and type B (FtsH2 and FtsH8) proteins, and the subunits in the same type are functional redundancy, while those in the different type are not interchangeable (Sakamoto 2003;Yu et al 2004;Zaltsman et al 2005). The well-known function of the FtsH protease is to degrade D1 protein during PSII repair (Yu et al 2004;Kato et al 2009Kato et al , 2012Kato and Sakamoto 2014). However, available evidence suggests that the role of FtsH2/ VAR2 in chloroplast development is independent of its protease activity on D1 degradation (Zaltsman et al 2005;Zhang et al 2009;Kato et al 2009Kato et al , 2012Kato and Sakamoto 2014).…”
Section: Introductionmentioning
confidence: 99%
“…These observations have led to the idea that PSII phosphorylation prevents excessive D1 degradation to avoid the accumulation of cytotoxic cleavage intermediates. Furthermore, given that phosphorylation of PSII core proteins can promote PSII migration and disassembly through structural remodeling of the thylakoid membrane to facilitate D1 access to the proteases (Kirchhoff, 2013), it is plausible that PSII phosphorylation fine-tunes the repair cycle by balancing D1 presentation and degradation (Kato and Sakamoto, 2014). How PSII phosphorylation modulates D1 proteolysis requires further investigation.…”
Section: Psii Repair Cycle On the Thylakoid Membranementioning
confidence: 99%
“…The phosphorylation and dephosphorylation of these proteins require the thylakoid-associated Ser/Thr kinase STATE TRANSITION8 (STN8; Bonardi et al, 2005) and the stroma/thylakoid-localized PROTEIN PHOSPHATASE 2C-TYPE PSII CORE PHOSPHA-TASE (PBCP; Samol et al, 2012). Lack of STN8 results in enhanced Deg-dependent D1 fragmentation under high-light conditions (Kato and Sakamoto, 2014), whereas PBCP defects cause delayed D1 degradation in high light (Samol et al, 2012). Levels of smaller, intermediary D1 fragments are correlated with ROS accumulation, suggestive of their cytotoxicity.…”
Section: Psii Repair Cycle On the Thylakoid Membranementioning
confidence: 99%